The calcium binding S100B protein as a new modulator of amyloid-β peptide aggregation - Cristóvão, Joana Margarida Lopes da Silva (2019)
Amyloid aggregation and chronic neuroinflammation are pathological hallmarks in Alzheimer’s disease. Interestingly, important neuronal components such as pro-inflammatory cytokines and transition metal ion levels are also consistently deregulated in AD. S100B is the most abundant pro-inflammatory cytokine in the brain and acts as an alarmin in AD, being upregulated and around amyloid plaques. In this PhD thesis we aimed at targeting the role of S100B over extracellular aggregation of amyloid-β at early stages of AD and at understanding the influence of metal ions over these regulatory processes. We found that S100B acts as a new modulator of Aβ aggregation and toxicity and exhibits some features similar to molecular chaperones. This regulatory action is activated by calcium or zinc-binding to S100B as by its quaternary state. We developed single-domain antibodies targeting S100B that increase the suppressor effect of S100B over the onset and progression of Aβ aggregation. Additionally, we also designed and synthetized S100Bbased peptides that can induce S100B oligomerization as a mean to control S100B levels in the brain. Moreover, we explored the potential effects of S100B in the synaptic cleft by performing assays in primary hippocampal neurons where S100B chelate zinc ions from the medium, contributing to changes in the postsynaptic scaffold Shank proteins, proteins essential to the maintenance of synapse plasticity. We generate new scientific and technological knowledge with potential applicability in human health, as S100B-based molecules can be used as a new druggable target to slow down AD progression and lead to diseasemodifying therapies.